2012
DOI: 10.1262/jrd.11-138n
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Redox Regulation on <i>In Vitro</i> Development of Mammalian Embryos

Abstract: Abstract. Many factors affect development of mammalian preimplantation embryos in vitro. It is well known that in vitro development of bovine embryos is highly affected by culture condition including energy source, growth factors, pH or gas environment. Many efforts have been made towards the suitable environments which can successfully support embryo development in vitro. For a rapid growth and differentiation, embryo requires energy by utilizing ATP, NADPH with oxygen molecules. These energy substrates are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
184
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(210 citation statements)
references
References 129 publications
(106 reference statements)
5
184
0
6
Order By: Relevance
“…These enzymes abase primary ROS, such as superoxide anion and hydrogen peroxide, before they can interact to form more reactive cytotoxic metabolites. 27 Previous studies have shown that I/R causes an increase in MDA levels and a decrease in GSH levels and SOD activity. 28,29 Similarly, we observed a significant decrease in GSH levels and SOD activity and an increase in MDA content during I/R-induced renal injury, making our findings agree with results from previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…These enzymes abase primary ROS, such as superoxide anion and hydrogen peroxide, before they can interact to form more reactive cytotoxic metabolites. 27 Previous studies have shown that I/R causes an increase in MDA levels and a decrease in GSH levels and SOD activity. 28,29 Similarly, we observed a significant decrease in GSH levels and SOD activity and an increase in MDA content during I/R-induced renal injury, making our findings agree with results from previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…2 ROS production is controlled by enzymatic and nonenzymatic processes. 4 Superoxide dismutase (SOD) and glutathione (GSH) are, respectively, one of the enzymatic and non-enzymatic antioxidants. 4 Oxidative stress is the usual phrase used to identify the association of the toxic free radicals with damage to cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…4 Superoxide dismutase (SOD) and glutathione (GSH) are, respectively, one of the enzymatic and non-enzymatic antioxidants. 4 Oxidative stress is the usual phrase used to identify the association of the toxic free radicals with damage to cells and tissues. 5 There are controversial results of antioxidant and oxidant system status after I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced GPX3 expression can result from elevated production of ROS and is associated with an increased risk of damage to mitochondrial and nuclear DNA, which can lead to developmental retardation and arrest (Takahashi 2012). Although there were no significant differences in GPX3 expression in oocytes recovered from younger versus older mares, and no significant effect of in vitro oocyte maturation on GPX3 expression, relative gene expression for GPX3 was approximately halved after IVM.…”
Section: Discussionmentioning
confidence: 90%
“…This increase may therefore indicate a response to a suboptimal environment (in vitro culture) aimed at maintaining sufficient mtDNA and mitochondria to safeguard embryonic development. Under suboptimal conditions, ROS production is likely to be higher, resulting in an increased risk of mtDNA damage; an increase in mtPOLB expression could therefore be a reaction to mitigate mtDNA damage (Takahashi 2012;Giritharan et al 2007).…”
Section: Discussionmentioning
confidence: 99%